Four-millimeter implants supporting unsplinted metal-ceramic screw-retained crowns in posterior jaw: a retrospective case series - Pinhata-Baptista, Otavio Henrique; Monteiro da Silva, Felipe; Goulart Gil Choi, Isabela; Rodriguez Gonzalez Cortes, Arthur (Scientific Letters, 2024)
Little is known about the clinical performance of unsplinted crowns supported by 4-mm implants. The objective of this investigation was to evaluate the clinical performance of extra-short implants supporting single restorations. A retrospective cross-sectional study design was used and included patients treated with 4-mm implants between 2014 and 2017. The influence of crown-to-implant ratio (CI ratio), age, sex, bleeding on probing, type of arch, implant diameter, occlusion antagonist and functional loading time on mesial and distal marginal bone loss around the implants were analyzed using univariate and multivariate linear regression models. A total of 27 cone morse dental implants with 4 mm was evaluated after a minimum post-loading time of 12 months. One implant was lost after loading, leading to an implant survival percentage equal to 96,3%. No other failure conditions were observed. From the variables analyzed herein, only CI ratio, functional loading time and sex were significantly associated with marginal bone loss on the mesial site of implants; and only CI ratio, functional loading time and bleeding on probing were associated with marginal bone loss on the distal site of implants. The present results suggest that 4-mm implants placed in the posterior maxilla and mandible to support unsplinted metal-ceramic screw-retained crowns may be a very promising alternative in order to enable the rehabilitation of posterior edentulous patients, who are unable or unwilling to undergo bone grafting procedures with high morbidity. However, further prospective long-term studies should confirm if this is a viable treatment option.